Biblionyms in the Epic "Layli and Majnun" (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article describes the lexical features of biblionyms in Alisher Navoi's epic "Layli and Majnun". The onomastic scope of the epic, i.e., the issues of using proper nouns, was analyzed.